Pemanfaatan Metode TOPSIS dalam Membangun Sistem Pendukung Keputusan untuk Menentukan Jenis Penyakit Tanaman Gandum; Studi Kasus di Ladang Gandum Alahan Panjang, Sumatera Barat - Akbar, Ricky; Sari, Silvia P; Denta, Dhiya N (Universitas Pattimura, 2024)
Wheat (Triticum aestivum L.) is an annual plant that can grow in highland areas. There are many types of diseases that attack wheat plants, making it difficult for farmers to determine the type of disease. Therefore, it is necessary to build a Decision Support System (DSS) that can determine the type of disease that attacks wheat plants. This research aimed to design and develop a Decision Support System (DSS) application to identify the types of diseases affecting wheat by observing the physical characteristics of the plants. These disease characteristics (criteria) were then inputed into the system, which used an algorithm based on the Technique for Order of Preference by Similarity to a Ideal Solution (TOPSIS) method. The DSS method used was TOPSIS, which considered four criteria: Flower, Stem, Seed, and Leaf. The application development method for the DSS used the Waterfall model, which consisted of the following stages: requirements, definition, system and software design, implementation, and unit testing. A DSS application using the TOPSIS method can determine the type of wheat disease based on physical characteristics as criteria that are inputed into the application. This application can help wheat farmers identify the diseases affecting their plants. The use of the TOPSIS method algorithm in developing the SPK application is an innovation that can help Alahan Panjang wheat farmers in detecting diseases types affecting their crops based on visible physical characteristics. Automatically, the system provides recommendations on the type of disease affecting the wheat plants.